Peningkatan Hasil Belajar Matematika Melalui Penggunaan Puzzle Rumah Perkalian Di Kelas II Sekolah Dasar - Venni Herli Sundi; Herwina Bahar (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2020)
In the process of carrying out the research, researchers looked at the ability of students to learn mathematics in SD Kramat Jati 24 East Jakarta, especially in multiplication counting operations. This condition is caused by a lack of motivation and curiosity of students in mathematics subjects, so that student learning outcomes are still not maximal. To find out the increase in student learning outcomes in calculating operating material using puzzle house multiplication media is the purpose of the study. The method is class action research with the Kemmis & Taggart model. The results of the study obtained an increase in the percentage of KKM achievement from preclusions of 28.4% where in the KKM cycle students only 65.5% got an increase to 78.1% in the first cycle and in the second cycle they got an increase to 94%. This shows that the use of multiplication house puzzles in mathematical counting operating materials can improve learning outcomes and make students more creative and effective. Researchers hope the results of this study can be useful for readers, for teachers, for parents and other education practitioners in guiding students in the learning process.